Pemberdayaan UMKM Dalam Menstabilkan Perekonomian Daerah Rejang Lebong di Tengah Pandemi Covid-19 - Ranaswijaya, Ranaswijaya (Disclosure: Journal of Accounting and Finance, 2022)
This paper aims to describe how efforts are made to empower Micro, Small, and Medium Enterprises (UMKM) in stabilizing the economy in the midst of the Covid-19 pandemic. The data used is sourced from data from the official website of several agencies or institutions that are relevant to this research. The results show that although the Covid-19 pandemic has created problems for UMKM and cooperatives, on the other hand, opportunities have also emerged. UMKM actors and cooperatives can take advantage of information and communication technology so that creativity and innovation emerge among UMKM in maintaining their business which has an impact on the optimal use of local or regional products. Local governments seek to empower UMKM in meeting community needs through skills development programs and funding assistance. The UMKM empowerment programs in the midst of the Covid-19 pandemic include changing business models from conventional to digitalization, designing social and digital strategies, developing and empowering UMKM resources optimally, and economic recovery programs in the form of capital assistance from the government.